E-campus UiTM online shopping using mobile application / Muhammad Firdaus Mohd Ismail - Mohd Ismail, Muhammad Firdaus (2020)
Nowadays, the students are having problem in getting information in the Whatsapp Group. It is because, sometimes the group chat was flooded with the business advertisement or else. So that the others student will miss the important information and took some time to find back the information. This project aims to develop a dedicated mobile application that focused on students who wants to sell their products. Moreover, this application also can be a side income for students who wants to start their business or want to an entrepreneur. Besides, this mobile application will be implemented using android operating system because most of the students are using android operating system on their smartphone. This project applies the Agile Software Development as the methodology to develop the application. This model contains six phases such as plan, design, develop, test, release and feedback. But for the proposed project just involves four phases only start from plan phase until test phase. Lastly, after this project is completely develop, the application is expected to be used by students and can provide a dedicated platform for their business advertisement.